Opportunist pulmonary infection with Legionella bozemanii. Issue 5 (May 1989) - Swinburn, C R; Gould, F K; Corris, P A; Hooper, T L; Odom, N J; Freeman, R; McGregor, C G
Abstract : Three cases of pulmonary Legionella bozemanii infection in immunocompromised patients are described. The diagnosis was made by culture in each case and would not otherwise have been made, and it is recommended that a culture specific for Legionella species should be included in the investigation of patients with suspected opportunist pulmonary infections.